Prevalence, indications and management of balloon uncrossable chronic total occlusions: Insights from a contemporary multicenter US registry. Issue 1 (21st September 2016) - Karacsonyi, Judit; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Jaffer, Farouc A.; Yeh, Robert W.; Patel, Mitul; Bahadorani, John; Doing, Anthony; Ali, Ziad A.; Karatasakis, Aris; Danek, Barbara A.; Rangan, Bavana V.; et al.
Abstract : Background: Balloon uncrossable lesions can be challenging to treat, requiring specialized techniques and equipment. Methods: We examined the prevalence, clinical and angiographic characteristics, management and procedural outcomes of balloon uncrossable lesions in a multicenter chronic total occlusion (CTO) percutaneous coronary intervention (PCI) registry. Results: Between 2012 and 2016, 718 CTO PCIs (in which the occlusion was successfully crossed with a guidewire) were performed in 701 patients at 11 US centers. Mean age was 65.6 ± 10 years and 84% of the patients were men. Balloon uncrossable lesions represented 9% of all CTOs. Balloon uncrossable CTOs had more moderate/severe calcification (82% vs. 52%, P  < 0.0001), moderate/severe tortuosity (61% vs. 35% P  < 0.0001) and higher J‐CTO score (2.95 ± 1.32 vs. 2.43 ± 1.23, P  = 0.005) as compared with the remaining lesions. Technical and procedural success was significantly lower for balloon uncrossable lesions (90.5% vs. 98.3%, P  < 0.0001 and 88.9% vs. 96.6% P  = 0.004), respectively, but the incidence of major adverse events was similar (1.6% vs. 2.2%, P  = 0.751). Balloon uncrossable lesions required longer procedure (208 [interquartile range: 135, 258] vs. 135 [94, 194] min, P  < 0.0001) and fluoroscopy (77 [52, 100] vs. 45 min [27, 75], P  < 0.0001) time. Techniques used to treat balloon uncrossable lesions included balloon‐assisted microdissection (23%), excimer laser atherectomy (18%), and rotational atherectomy (16%). Excimer laser atherectomy and balloon‐assisted microdissection were associated with the highest technical and procedural success rates. Conclusions: Balloon uncrossable CTOs are common, are associated with high rates of technical failure, and require specialized techniques for successful treatment. © 2016 Wiley Periodicals, Inc.